2020
DOI: 10.1001/jamaophthalmol.2020.1902
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of a Primary Open-Angle Glaucoma Prediction Model Using Long-term Intraocular Pressure Variability Data

Abstract: for the European Glaucoma Prevention Study and the Ocular Hypertension Treatment Study IMPORTANCE The contribution of long-term intraocular pressure (IOP) variability to the development of primary open-angle glaucoma is still controversial. OBJECTIVE To assess whether long-term IOP variability data improve a prediction model for the development of primary open-angle glaucoma (POAG) in individuals with untreated ocular hypertension. DESIGN, SETTING, AND PARTICIPANTS This post hoc secondary analysis of 2 randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 36 publications
0
17
0
1
Order By: Relevance
“…The significance of diurnal IOP fluctuation and the development of glaucomatous damage has yet to be fully established in the literature. [86][87][88][89][90][91][92][93][94][95][96] Additional IOP measurements may be indicated, either at different hours of the day on the same day or on different days. Larger inter-eye asymmetry of IOP has also been shown to be a risk for developing glaucoma.…”
Section: Intraocular Pressure Measurementmentioning
confidence: 99%
“…The significance of diurnal IOP fluctuation and the development of glaucomatous damage has yet to be fully established in the literature. [86][87][88][89][90][91][92][93][94][95][96] Additional IOP measurements may be indicated, either at different hours of the day on the same day or on different days. Larger inter-eye asymmetry of IOP has also been shown to be a risk for developing glaucoma.…”
Section: Intraocular Pressure Measurementmentioning
confidence: 99%
“…Notably, patients in the medically treated group had a 3– to 4–mm Hg higher IOP than that of the surgically treated group, conversely suggesting that IOP variability is a more important factor in patients with higher IOP. While the above 2 studies investigated the role of IOP variability in patients with glaucoma, other studies evaluated the role of IOP variability in the development of glaucoma . Medeiros and colleagues found no association between the development of glaucoma and IOP variability in eyes with untreated ocular hypertensive .…”
Section: Discussionmentioning
confidence: 99%
“…Long-term IOP variability can be obtained from repeated IOP measurements taken at serial office visits over months to years. Findings from prior studies have been inconclusive based on assessment of the association between long-term IOP variability and visual field (VF) progression using subjective assessment of standard automated perimetry and/or photograph-based optic disc changes …”
Section: Introductionmentioning
confidence: 99%
“…Predicting glaucoma onset and progression is a major clinical challenge. Previous studies demonstrated that biometric parameters, such as baseline IOP, vertical cup-to-disc ratio, mean deviation (in the Humphrey visual field test), and pattern standard deviation are helpful in predicting glaucoma incidence and progression ( 6 12 ). However, IOP measurement and visual field tests are often not available in the primary healthcare setting.…”
Section: Introductionmentioning
confidence: 99%